Multistatic radar system design and simulation - U Tint Wan (2008)
The main idea of Multistatic Radar System is to look for target’s geodetic position without failing detection of target echo caused by interference. A Multistatic Radar uses two or more receiving sites because one receiver fails to detect targer’s echo, the others will detect and locate target’s echo.